Innovative microencapsulation of hemp seed oil using plant-based biopolymers: A comparative analysis of dehydration techniques on core stability, digestibility and release pattern - Gholivand, Somayeh; Tan, Tai Boon; Yusoff, Masni Mat; Qoms, Mohammed S.; Wang, Yong; Liu, Yuanfa; Nyam, Kar Lin; Tan, Chin Ping (Elsevier B.V., 2025)
This study explores various dehydration methods, including freeze drying (FD), spray drying (SD), and the supercritical carbon dioxide solution-enhanced dispersion (SEDS) process, to encapsulate hemp seed oil (HSO) within a complex matrix of hemp seed protein isolate and alginate. One noteworthy aspect of this study involves the in-depth analysis of the structural characteristics of the delivery systems, highlighting their pivotal role in shaping HSO release patterns. The findings indicate that SEDS microcapsules (SEDS-M), with their smallest particle size and smooth, spherical morphology, effectively preserved structural integrity and provided controlled oil release across diverse pH levels (3–9) and salt concentrations (0–200 mM). During the gastrointestinal phases, minimal oil release occurred during oral digestion (<25%) for all samples, while the significant gastric release occurred in FD (39.8%) and SD microcapsules (33.4%). With their highest storage stability, SEDS-M demonstrated superior delayed and sustained release (27.9%) during gastric transit, making them ideal for protecting sensitive ingredients and ensuring targeted intestinal delivery.